ABCA7 PTC mutation carriers present with Alzheimer's disease pathology and cerebral amyloid angiopathy: Basic science and pathogenesis: Genetics and omics of AD. (7th December 2020) - Hens, Elisabeth; Bossaerts, Liene; Sieben, Anne; Bossche, Tobi Van den; Engelborghs, Sebastiaan; Peeters, Karin; Vermeiren, Yannick; De Roeck, Naomi; Hanseeuw, Bernard J.; Vandenberghe, Rik; Deyn, Peter Paul De; Cras, Patrick; et al.
Abstract: Background: Genetic screening of our Belgian Alzheimer's Disease (AD) cohort (n = 1478) observed in 69 patients, 15 different premature termination codon (PTC) mutations in the gene coding ATP‐Binding Cassette Subfamily A Member 7 (ABCA7) leading to loss of ABCA7 protein. We aimed to delineate the clinicopathological AD phenotype of the ABCA7 mutation carriers. The ABCA7 gene was initially identified as a risk gene in genome wide association studies of large AD patient cohorts. Methods: Reviewing of available demographic and (n = 44) clinical data (n = 64), neuroimaging studies (n = 62), CSF analysis (n = 28) and neuropathological (n = 10) data. Result: The 69 ABCA7 carriers had a mean onset age of 69.5 ± 9.7 years. In 68 carriers, onset age ranged from 48 to 90 years and mean disease duration was 8.1 ± 4.3 years (range 1‐18). APOE genotypes did not have a modifying effect. A positive familial disease history was noted in 75.0% of carriers. Most carriers displayed an amnestic phenotype (87.6%) without clear distinctive features in clinical examination or neuroimaging. Cerebrospinal fluid (CSF) biomarkers were available for 28 carriers, showing an AD profile in 82.1% of patients. Additional (re)analysis of CSF biomarkers is ongoing for 36 carriers, including Aβ1‐42 /Aβ1‐40 ratio as an ancillary biomarker. Imaging features compatible with cerebral amyloid angiopathy (CAA) were described in 3 patients, and 2 other patients suffered from (a) lobar hemorrhage(s). Chronic microvascular damage was noticed in 78.2% of patients. Brain autopsy revealed typical AD pathology together with CAA in all 10 carriers. High levels of CAA were present in both the meningeal and capillary blood vessels, and moderate to high levels of CAA in the parenchymal blood vessels. Further, CAA was not limited to the occipital brain region, but extended to the other neocortices and even to the medial temporal region (n = 5). CAA did not correlate with the levels of AD pathology or APOE genotype. Conclusion: Carriers of ABCA7 PTC mutations present with a classical AD phenotype, although with a wide onset‐age, even for carriers of the same mutation. Neuropathological examination revealed extensive levels of CAA in all 10 autopsied brains, additional to AD pathological hallmarks. These findings have important implications for future research and clinical practice.